A case of atypical thymic carcinoid mimicking a paraganglioma. (2020) - Yasukawa, Motoaki; Uchiyama, Tomoko; Kawaguchi, Takeshi; Sawabata, Noriyoshi; Ohbayashi, Chiho; Taniguchi, Shigeki
Graphical abstract: Highlights: Preoperative diagnosis of thymic epithelial tumours is challenging. Atypical carcinoid and paraganglioma are similar-appearing. Thymic atypical carcinoid has high recurrence and metastasis rates due to frequent lymph node metastases. Thymic atypical carcinoid should be considered when positron emission tomography/computed tomography shows high-uptake tumours. Clinicians should consider using the Median sternotomy approach, even if the tumour is <5 cm. Abstract: Background: Thymic atypical carcinoid has high recurrence and metastasis rates due to frequent lymph node metastases. The aim of the study is to report a case of atypical thymic carcinoid mimicking a paraganglioma and to further explain the benefits of using median sternotomy (MS) approach even in thymic epithelial tumours (TETs) sized less than 5 cm. Case presentation: The patient was a 59-year-old asymptomatic man. During a medical check-up, positron emission tomography/computed tomography (PET/CT) showed a 4.5 cm-diameter thymus with remarkable uptake. Thoracic surgery was performed to completely remove the tumour with lymph node dissection using MS because of possible malignancy. Although MS is accepted as the standard approach for TETs, minimally invasive thoracotomy (MIT) has emerged over recent decades. Maintaining surgical safety is priority; MIT is generally selected in <5-cm-diameter tumours. Here, we considered that the tumour could be resected using MIT. However, because PET/CT showed marked uptake, we selected the MS approach. Thus, MS can be applied even for small-sized TETs. Conclusion: Thymic atypical carcinoid should be considered when PET/CT shows high-uptake tumours in the anterior mediastinum. Clinicians should consider using the MS approach, even if the tumour is <5 cm.